In the land of Ninkasi: a history of beer in Mesopotamia - Paulette, Tate (Oxford scholarship online, 2024)
'In the Land of Ninkasi' tells the story of the world's first great beer culture. In this authoritative but light-hearted account, archaeologist Tate Paulette brings the world of ancient Mesopotamian beer into vivid focus. He weaves together insights drawn from archaeological remains, ancient works of art, and cuneiform texts and pulls the reader, step-by-step, into the process of analysis and interpretation, explaining exactly what we know and how we know it. Readers will learn about the beers themselves and how they were made, consumed, and stored, and how to recreate modern versions of Mesopotamian brews.